2016
DOI: 10.18869/acadpub.jrh.6.5.537
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and unintended pregnancy among rural Iranian women

Abstract: Health literacy is a significant element in the ability of a woman to engage in health promotion and preventive activities both for herself and her children. This study aimed to evaluate health literacy and the rate of unintended pregnancies, as well as the relationship between health literacy and unintended pregnancies among rural Iranian married women. This study was conducted on 240 rural married women aged 18 to 45 years. To collect data, the Persian version of the test of functional health literacy in adu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The results of this study were inconsistent with the study of Sajjadi et al, whose statistical population was rural women of Izeh city. Sajjadi and colleagues' study showed no significant relationship between health literacy and physical activity (16). This difference is probably because women with a lower level of education report their activity more.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The results of this study were inconsistent with the study of Sajjadi et al, whose statistical population was rural women of Izeh city. Sajjadi and colleagues' study showed no significant relationship between health literacy and physical activity (16). This difference is probably because women with a lower level of education report their activity more.…”
Section: Discussionmentioning
confidence: 88%
“…Health literacy and a healthy lifestyle are among the priorities of the Ministry of Health of Iran. In the vision plan of Iran Health Education and Promotion Office 1404, the first priority is increasing health literacy, and the second is a healthy lifestyle (16).…”
Section: Introductionmentioning
confidence: 99%
“…The result of inadequate HL on a poor physical function dimension of quality of life among patient with ischemic heart disease is shown in a study in Queensland and South Australia (31). HL may lead to a better lifestyle (32,33), more use of preventive care (34), and adherence to medical treatment (35).…”
Section: What Is Already Known On This Topicmentioning
confidence: 99%
“…Health literacy is one of the factors that directly affect women's health and an important factor in women's ability to promote their and their children's health (3). In examining health literacy levels in women of reproductive age, Jarrahi (2017) and Sajjadi (2016) showed that about 50% and 62% of the studied women had low (marginal and inadequate) levels of health literacy, respectively (4,5).…”
Section: Introductionmentioning
confidence: 99%